Gamification in Contextual Learning-Based Approaches: A Systematic Review of Empirical Research - Gracelda Luthfi Aurellia; Cecep Kustandi; Dwi Kusumawardani; Imam Fitri Rahmadi (Journal of Educational Sciences, 2026)
Gamification is widely used to increase student motivation and participation, yet evidence on its effective integration with Contextual Teaching and Learning (CTL) remains fragmented. This systematic review aims to map how gamification elements are integrated with CTL components and how the integration relates to reported learning outcomes. The review followed PRISMA 2020 guidelines through a structured search in Scopus, screening based on predefined inclusion and exclusion criteria, and methodological quality assessment prior to synthesis. Included studies were analyzed narratively by coding gamification elements, CTL implementation (authentic context, inquiry/discovery, collaboration, and reflection), research design, educational level, and outcome indicators. The synthesis suggests that integration is most consistently associated with positive outcomes when game elements are embedded in authentic, context-rich tasks and inquiry-oriented activities, supported by clear learning goals and formative feedback. However, the current evidence base is constrained by limited coverage of early childhood education, short intervention durations, and incomplete reporting of implementation fidelity. Future research should expand educational contexts, improve transparency in documenting CTL enactment and gamification use, and apply longer-duration designs to evaluate sustained outcomes.